Internet para a terceira idade: novos tempos, para aprender, nunca é tarde - Horioka, Vinicius Paiva [UNESP]; Dotta, Edivani Aparecida Vicente [UNESP]; Pinelli, Camila [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: The technology is increasingly present in people's lives, regardless of their wishes. If a few years the use the Internet was a privilege of some, today it has become a necessity bringing in most of the time, numerous benefits to people and could not be different in third age. The use of the Internet leads to having new knowledge without giving up their habits and customs: discover and reconnect to relatives and friends, besides being excellent mental exercise because there is always something new to learn. Objective: The project aims to include the elderly in the digital age, using the computer and the Internet tool to enhance their intellectual and physical abilities, providing a learning experience for a virtual communication through e-mail, social networking and search sites, opening, therefore, new horizons. Methods: The population is composed of individuals of both sexes, aged 55 or older, coming from the Open University of the Third Age (UNATI). At the beginning of the course is assigned a self-assessment questionnaire and the information stored by the scholarship student in Access database system. After the analysis, it can be observed a breakthrough in terms of knowledge and personal satisfaction among the elderlies. Results and Discussion: The course has offered classes for 13 years to approximately 260 students. They have explored basic computer tasks such as using the mouse, the keyboard and the pen-drive. They have also learned how to use the Internet through common tasks such as opening a website, writing, reading and sending e-mail, and attaching files, creating groups and getting together. In addition, basic computer commands are thought and they are related to how to create folders, how to explore them, open and delete them, and also how to execute the commands of copy, paste and delete files within folders. Some information on social networks and digital photographs has been thought too. Theoretical and practical classes are weekly held in the Computer Didactic Laboratory (LDI) at the Faculty of Dentistry of Araraquara - UNESP. Each class lasts 120 minutes. During the classes the scholarship student takes pictures and makes movies of the students’ activities at UNATI. This scholarship student also assists the elderly students during their classes, and he collaborates with the preparation of courseware. The project also relies on the volunteers. The possibility of virtual communication and learning technologies that make the elderlies more independent in their daily tasks are the reasons that stand out in the search of the course by this group of students. Conclusion: In these thirteen years of the project it can be concluded that it has been promoting the improvement in knowledge and in computer skills among the elderly participants.

Introdução: A tecnologia está cada vez mais presente na vida das pessoas, independentemente de seus desejos. Se há alguns anos o uso da Internet era privilégio de alguns, hoje ela tem se tornado uma necessidade trazendo, na maioria das vezes, inúmeros benefícios às pessoas e não poderia ser diferente na terceira idade. O uso da Internet os leva a ter novos conhecimentos sem deixar de lado os seus hábitos e costumes: descobrir e reaproximar-se de parentes e amigos, além de ser excelente exercício mental, pois há sempre uma coisa nova a se aprender. O projeto iniciou-se em 2003. Objetivo: Incluir o idoso na era digital, utilizando a ferramenta computador e a Internet para melhorar suas habilidades intelectuais e físicas, propiciando um aprendizado para uma comunicação virtual por meio de e-mail, rede social e sites de pesquisa, abrindo, portanto, novos horizontes. Material e Método: A população é composta por indivíduos, de ambos os sexos, com idade igual ou superior a 55 anos, oriundos da Universidade Aberta da Terceira Idade (UNATI). No início e no final do curso é aplicado um questionário de autoavaliação sendo as informações armazenadas pelo bolsista no sistema de banco de dados Access, possibilitando após análise, avaliar seu conhecimento e satisfação pessoal. Resultados e Discussão: O curso, oferecido há treze anos, totaliza aproximadamente 260 alunos, explora tarefas básicas do computador como a utilização do mouse, teclado e pen-drive. Para utilizar a Internet aprendem tarefas comuns tais como: abrir um site; escrever, ler e enviar um e-mail e anexar arquivo no mesmo; criar grupos e inserir contato. Além disso, são explorados comandos básicos do computador como criar, abrir e deletar pastas; copiar, colar e deletar arquivo dentro das pastas. Informações sobre redes sociais e fotografias digitais também foram inseridas. As aulas são ministradas semanalmente no Laboratório Didático de informática (LDI), na Faculdade de Odontologia de Araraquara - UNESP, todas teóricas-práticas, com aulas semanais de 120 minutos cada. Durante as aulas o bolsista realiza filmagens e fotos nos momentos das atividades e lazer, além de auxiliar os alunos durante as aulas e colaborar na preparação do material didático e diário das aulas. O projeto também conta com voluntários. A possibilidade de comunicação virtual e o aprendizado de tecnologias que os tornam mais independentes em suas tarefas diárias são os motivos que mais se destacam na procura do curso por parte dos alunos. Conclusão: Nesses treze anos de projeto pode-se concluir que o mesmo promove melhorias nos conhecimentos e habilidades em informática nos indivíduos participantes.
Keywords: Internet; Education; Third age; Internet; Educação; Terceira idade